Uranium and thorium behavior in groundwater of the natural spa area "Choygan mineral water" (East Tuva) - Kopylova, Yuliya Grigorievna; Guseva, Natalia Vladimirovna; Shestakova, Anastasiya Viktorovna; Khvaschevskaya, Albina Anatolievna; Arakchaa, K. (IOP Publishing, 2015)
The natural spa area "Choygan mineral waters", a unique deposit of natural carbon dioxide mineral waters in Siberia, is located in the Eastern Sayan Mountains. There are 33 spring discharges in this area. Spring waters are mainly of HCO[3]-Na-Ca type. TDS varies from 300 mg/L to 2600 mg/L, the temperature ranges from 7 °С (in spring 33) to 39 °С (in spring 12), pH varies from 5.9 to 8.3, and the value of the oxidation-reduction potential is from -170 mV to 236 mV. All studied waters were divided into two groups according to their temperature and geochemical conditions: cold fresh water in oxidizing environment and warm slightly brackish water in reducing environment. The uranium concentration varies from 0.7 to 14 [mu]g/l and the thorium concentration varies from 0.001 to 0.33 [mu]g/l in the studied waters. The predominant uranium complexes are (UO[2](CO[3])[3]){4-}, (UO[2](CO[3])[2]){2-}, UO[2]CO[3], (UO[2](PO[4])[2]){4-} in the waters in oxidizing and reducing environments. It was found that acid-alkaline and oxidizing-reducing conditions were the determining factors for uranium behavior and speciation in the studied waters. The pH conditions are determining factors for thorium behavior and speciation in the studied waters. In slightly acidic water the predominant thorium species is negatively charge complex (ThCO[3](OH)[3])- (more than 95 %).
Keywords: уран; торий; грунтовые воды; Восточная Тува; минеральные воды; углерод